2023
DOI: 10.3390/jcm12093079
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in Pregnant Mothers’ Attitudes and Willingness to Donate Umbilical Cord Stem Cells: A Cross-Sectional Analysis from Saudi Arabia

Abstract: The collection and storage of umbilical cord stem cells (UCSCs) have a crucial role in improving and expanding stem cell-based therapies, which are becoming popular in Saudi Arabia and other Middle East countries. Many patients and families in Saudi Arabia depend on private cord banks in foreign countries to purchase stem cells, which has financial and medical implications. The current study aims at determining the predictors of current registration status and willingness to donate cord blood stem cells among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The integrative review by Peperdy et al 12 had led to the same conclusion. Other authors 13,14 furthermore underlined the importance of raising more awareness among medical professionals in order to be able to provide correct and differentiated pieces of information to expecting parents, directing them to reliable sources and increasing their knowledge regarding UCB donation or storage.…”
Section: Discussionmentioning
confidence: 99%
“…The integrative review by Peperdy et al 12 had led to the same conclusion. Other authors 13,14 furthermore underlined the importance of raising more awareness among medical professionals in order to be able to provide correct and differentiated pieces of information to expecting parents, directing them to reliable sources and increasing their knowledge regarding UCB donation or storage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of people's knowledge, comprehension, preferences, and attitudes regarding CB banking have been carried out in different countries. The majority of those findings indicate a lack of public awareness, with mothers and even medical professionals and other healthcare providers assumed to be knowledgeable about it [14][15][16][17][18][19][20][21][22][23]. Therefore, the primary purpose of the present study is to determine the level of knowledge of SCB among the Saudi Arabian population.…”
Section: Introductionmentioning
confidence: 99%
“…Other local studies assessed the knowledge and attitudes of medical professionals and nursing students [ 14 , 15 ]. In our prior national study, we found that rates of registration for donation umbilical cord stem cells among pregnant women in Saudi Arabia was just around one percent [ 16 ]. It is, therefore, of prime significance to study current levels of knowledge about sources of stem cells and donor agencies among different sub-populations from geographical regions which have not been explored earlier.…”
Section: Introductionmentioning
confidence: 99%